2022
DOI: 10.3390/app12115298
|View full text |Cite
|
Sign up to set email alerts
|

Occupants’ Perspectives of the Use of Smartphones during Fire Evacuation from High-Rise Residential Buildings

Abstract: Over the past few years there has been a significant change in fire safety design and management. As the possibility of safe escape is the most crucial aspect of a building’s fire safety features, the understanding of human behaviour under fire conditions is important for a successful evacuation. Previous research studies have developed models, prototypes, and serious games that help engineers/architects to design or firefighters to improve design so that the building facilitates a smooth evacuation process. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The issue of fire escape becomes increasingly crucial in safety management as the number of high-rise structures rises. Traditional fire escape methods may lead to untimely evacuation and improper choice of escape routes when facing the challenges of high-rise buildings, threatening the lives of residents [5]. However, IoT technology offers new solutions for fire escape in high-rise buildings.…”
Section: Problem Statementmentioning
confidence: 99%
“…The issue of fire escape becomes increasingly crucial in safety management as the number of high-rise structures rises. Traditional fire escape methods may lead to untimely evacuation and improper choice of escape routes when facing the challenges of high-rise buildings, threatening the lives of residents [5]. However, IoT technology offers new solutions for fire escape in high-rise buildings.…”
Section: Problem Statementmentioning
confidence: 99%
“…In terms of new methods, Gerges et al [19] and Minji et al [20] observed the impact of dynamic emergency clues on evacuation, and sent the evacuation instructions directly to the mobile phones of the evacuees through customization to intelligently find the best exit route for evacuation. Fang et al [21] discussed the advantages and disadvantages of current intelligent fire evacuation by using the Internet of Things.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, lack of awareness makes building users not to feel the need to prepare for fire incidents and this makes make them nonchalant about the availability or unavailability and use of firefighting equipment and appurtenances, they also see no need to get trained for fire safety (Zhou, 2017). Gerges et al (2022) opined that the principal aim of FDP is to present a safe environment for all building users at all times in the building. Careful and orderly evacuation is important in order to protect occupants of a building during a fire incident (Jetvic, 2021).…”
Section: Introductionmentioning
confidence: 99%